35.4: Research of Evaluation Method of Display Temporal Characteristics. (4th October 2019) - Tang, Xian; Song, Li; Wu, Di; Pan, Jiangen
Abstract : Conventional methods to evaluate temporal characteristics of displays are found to be insufficient based on plenty of practical measurement, and can not match with the latest development of photobiological theory. In this paper, the drawbacks of current methods for temporal characteristics of displays were analyzed, and we proposed some supplementary methods for flicker, response time and motion blur, which makes the temporal characteristics measurement and evaluation more comprehensive and objective. Furthermore, we provided an display response time analyzer especially for display temporal characteristics test, which have been used for a series of display measurement in this article.